18F-FET PET/CT as a Diagnostic Tool for Brain Abscess. (October 2021) - Kang, Seo Young; Jang, Yunejeong; Cho, Min-Sun; Park, Soo Jeong; Moon, Byung Seok; Kim, Hye Ok; Yoon, Hai-Jeon; Kim, Bom Sahn
Abstract : Abstract: A 49-year-old man presented with sudden right-sided weakness and seizure. Brain MRI identified a lobulated mass with diffusion restriction and irregular wall enhancement in the left parietal lobe. 18 F-FET ( O -(2-[ 18 F]fluoroethyl)-L-tyrosine) PET/CT was performed, which identified a cystic mass in the left parietal lobe accompanied by FET uptake. Compartmentalized uptake was also confirmed throughout the left parietal lobe. Considering the relatively low target-to-background ratio and uptake observed in the entire left parietal lobe, the lesion was more likely to be a brain abscess than a tumor. The pathologic diagnosis after mass removal was acute and chronic inflammation with abscess.